Co-occurring Attention Deficit Hyperactivity Disorder symptoms in adults affected by heroin dependence: Patients characteristics and treatment needs. (April 2017) - Lugoboni, Fabio; Levin, Frances Rudnick; Pieri, Maria Chiara; Manfredini, Matteo; Zamboni, Lorenzo; Somaini, Lorenzo; Gilberto Gerra, .; Gruppo InterSert Collaborazione Scientifica (GICS),
Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a risk for substance use disorders. The aim of this study was to investigate the association between adult ADHD symptoms, opioid use disorder, life dysfunction and co-occurring psychiatric symptoms. 1057 heroin dependent patients on opioid substitution treatment participated in the survey. All patients were screened for adult ADHD symptoms using the Adult ADHD Self-Report Scale (ASRS-v1.1). 19.4% of the patients screened positive for concurrent adult ADHD symptoms status and heroin dependence. Education level was lower among patients with ADHD symptoms, but not significant with respect to non-ADHD patients. Patients with greater ADHD symptoms severity were less likely to be employed. A positive association was observed between ADHD symptoms status and psychiatric symptoms. Patients with ADHD symptoms status were more likely to be smokers. Patients on methadone had a higher rate of ADHD symptoms status compared to buprenorphine. Those individuals prescribed psychoactive drugs were more likely to have ADHD symptoms. In conclusion, high rate of ADHD symptoms was found among heroin dependent patients, particularly those affected by the most severe form of addiction. These individuals had higher rates of unemployment, other co-morbid mental health conditions, heavy tobacco smoking. Additional psychopharmacological interventions targeting ADHD symptoms, other than opioid substitution, is a public health need. Highlights: 19.4% Participants screened positive for concurrent adult ADHD symptom status and heroin dependence. Patients with greater ADHD severity were less likely to be employed. Patients with ADHD were more likely to be smokers. A positive association was observed between ADHD symptoms status and psychiatric symptoms. Patients on methadone had a higher rate of ADHD compared to buprenorphine. Patients prescribed psychoactive drugs were more likely to have ADHD symptoms.